Digitizing Heritage: Evaluating the Effectiveness of the Photoscan Method in Artifact Preservation at Lam Dong Museum, Vietnam - Nhan Phan; Phong Huy Le; Hoa Van Vu Tran (International Journal of Scientific Research in Civil Engineering, 2024)
The primary objective of this study is to evaluate the effectiveness of the PhotoScan method in digitizing artifacts at the Lam Dong Museum, producing high-quality 3D models that preserve the intricate details and historical significance of the original items. The research employs photogrammetry techniques to capture multiple high-resolution images of artifacts from various angles. These images are processed to create detailed 3D models, ensuring accuracy and fidelity to the original artifacts. Key findings reveal that the PhotoScan method successfully generates accurate and detailed digital replicas with minimal deviations from the physical artifacts, typically within acceptable limits of less than 1%. This level of precision confirms the reliability of PhotoScan in creating digital replicas suitable for various applications, including academic research, virtual exhibitions, and conservation efforts. Additionally, the study highlights the advantages of the PhotoScan method, such as its cost-effectiveness and accessibility, making it an attractive option for museums and institutions with limited budgets. The integration of high-resolution photographs into the 3D models further enhances their visual fidelity, providing realistic and detailed digital replicas. The study concludes that PhotoScan is a highly effective method for artifact digitization, offering significant benefits for museums in terms of preservation, public accessibility, and educational opportunities. The implications of these findings underscore the potential of PhotoScan technology to enhance the documentation and dissemination of cultural heritage in museum settings. Future research should focus on optimizing the workflow to reduce processing time and improve the handling of large datasets. The potential for 3D printing of digital models also presents exciting opportunities for creating accurate physical replicas for display and educational use while preserving the original artifacts.